(untitled) (The Review of Diabetic Studies, 2025)
Background: Children with complex medical needs require highly skilled and coordinated nursing care. Educational interventions are increasingly recognized as essential in preparing nurses to deliver effective and family-centered care. Objective: To systematically review empirical evidence on the impact of nursing education on the care of children with complex medical needs. Methods: Following PRISMA 2020 guidelines, a systematic search was conducted across PubMed, Scopus, Web of Science, CINAHL, and Google Scholar. Eligible studies included randomized controlled trials, quasi-experimental studies, cohort and cross-sectional analyses, and qualitative designs published between 2008 and 2024. Data extraction focused on study design, populations, interventions, and outcomes. Quality was assessed using the Newcastle-Ottawa Scale, Cochrane RoB 2, and CASP tools. Results: Twelve studies met inclusion criteria. Educational programs consistently improved nurses’ knowledge, attitudes, and clinical competencies in pediatric palliative care, nephrology, orthopedic surgery, and developmental screening. Family-focused educational encounters increased parental knowledge, attitudes, and caregiving practices. Broader outcomes included reduced hospital readmissions, fewer inpatient days, and lower healthcare costs. However, persistent gaps in novice nurse preparedness and inconsistencies in curriculum integration were identified. Conclusion: Nursing education is a critical determinant of care quality for children with complex medical needs. Structured, competency-based programs enhance professional practice, strengthen family engagement, and reduce health system utilization. Future efforts should prioritize curriculum reform, standardized definitions of complexity, and longitudinal studies to evaluate sustained outcomes.